Oral Health-Related Quality of Life, Locus of Control, Self-Reported Oral Health and Oral Health Status among Nursing Students in Moradabad - Jeevan Josh; K Thanveer; Supurna Pandit; Pallavi Divekar; Rakesh Kumar Pandey; Minakshi (Wolters Kluwer Medknow Publications, 2024)
Introduction: Oral health related quality of life (OHRQoL), locus of control, dental health as assessed by oneself and oral health situation have all been the subject of several research, but none of them have yet been investigated in combination. Materials and Methods: This cross-sectional study was carried out on 525 nursing students to investigate these ideas. The Oral Health Impact Profile-14 (OHIP-14) scale was employed to evaluate the standard of living associated with oral health. Results: Both chance participants and group internals reported having good OHRQoL. Nursing students in the internals group accurately assessed the deteriorated aspect of their self-reported oral health. However, it was found that participants from the chance locus and powerful others were unable to accurately rate the decayed component (P < 0.05). Conclusion: Internal nursing students had the highest OHRQoL, followed by random and influential students. Individuals from locus internals and random gave accurate ratings of their dental deterioration.